The Berenstain Bears go on a Ghost Walk - Berenstain, Stan, 1923-2005; Berenstain, Jan, 1923-2012. (New York : HarperFestival, 2005)
Papa Bear is enthused about preparing for Bear Country School's Halloween Ghost Walk, but learns that "one person's fun is another person's nightmare."
Recommended for ages 3-7.
Accelerated Reader
Keywords: Halloween -- Juvenile fiction; Bears -- Juvenile fiction